(untitled) (Biological Sciences - PJSIR, 2022)
Soil samples from one hundred and thirteen plant nurseries were collected for the detection of nematodes and their population threshold in China Orange. Citrus nematodes (Tylenchulus semipenetrans) which cause die back disease were found in abundance in association with other pathogenic nematodes viz, Helicotylenchus spp., Pratylenchus spp., Tylenchorhynchus spp. andXiphinema spp. Unhealthy plants were treated with Tenekil and DBCP for their comparative nematicidal study. Tenekil was found more effective.